The Trach Trail: A Systems-Based Pathway to Improve Quality of Tracheostomy Care and Interdisciplinary Collaboration. (August 2020) - Cherney, Rebecca L.; Pandian, Vinciya; Ninan, Ashly; Eastman, Debra; Barnes, Brian; King, Elizabeth; Miller, Brianne; Judkins, Samantha; Smith, Alfred E.; Smith, Nan M.; Hanley, Julie; Creutz, Eileen; et al.
Objective: To implement a standardized tracheostomy pathway that reduces length of stay through tracheostomy education, coordinated care protocols, and tracking patient outcomes. Methods: The project design involved retrospective analysis of a baseline state, followed by a multimodal intervention (Trach Trail) and prospective comparison against synchronous controls. Patients undergoing tracheostomy from 2015 to 2016 (n = 60) were analyzed for demographics and outcomes. Trach Trail, a standardized care pathway, was developed with the Iowa Model of Evidence-Based Practice. Trach Trail implementation entailed monthly tracheostomy champion training at 8-hour duration and staff nurse didactics, written materials, and experiential learning. Trach Trail enrollment occurred from 2018 to 2019. Data on demographics, length of stay, and care outcomes were collected from patients in the Trach Trail group (n = 21) and a synchronous tracheostomy control group (n = 117). Results: Fifty-five nurses completed Trach Trail training, providing care for 21 patients placed on the Trach Trail and for synchronous control patients with tracheostomy who received routine tracheostomy care. Patients on the Trach Trail and controls had similar demographic characteristics, diagnoses, and indications for tracheostomy. In the Trach Trail group, intensive care unit length of stay was significantly reduced as compared with the control group, decreasing from a mean 21 days to 10 ( P < .05). The incidence of adverse events was unchanged. Discussion: Introduction of the Trach Trail was associated with a reduction in length of stay in the intensive care unit. Realizing broader patient-centered improvement likely requires engaging respiratory therapists, speech language pathologists, and social workers to maximize patient/caregiver engagement. Implications for Practice: Standardized tracheostomy care with interdisciplinary collaboration may reduce length of stay and improve patient outcomes.